2020
DOI: 10.1093/jas/skaa125
|View full text |Cite
|
Sign up to set email alerts
|

Diet complexity and l-threonine supplementation: effects on growth performance, immune response, intestinal barrier function, and microbial metabolites in nursery pigs

Abstract: The aim of this study was to investigate the effects of diet complexity and l-Thr supplementation level on the growth performance, immune response, intestinal barrier function, and microbial metabolites in nursery pigs. Thirty-two weaned pigs (body weight 7.23 ± 0.48 kg) were randomly assigned to dietary treatments in a 2 × 2 factorial arrangement based on diet complexity (complex or simple) and dietary Thr content. The complex diet contained fish meal, plasma protein, and dried whey to mimic a conventional nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…One of the explanations for this effect might be that Thr promotes mucin secretion, because mucins cannot be digested in the small intestine and, therefore, arrive to the large intestine, where they serve as the substrates for saccharolytic bacteria [ 73 ]. Koo et al [ 74 ] found that the supplementation of Thr 15% higher than the NRC recommendation can interact with feed composition to alter gut microbial fermentation. The data also imply that Thr has beneficial effects on intestinal microbiota which might be related to mucin synthesis and immunoglobulin production as a result of Thr addition [ 72 ].…”
Section: The Roles Of Thr On Intestinal Health and Functionsmentioning
confidence: 99%
“…One of the explanations for this effect might be that Thr promotes mucin secretion, because mucins cannot be digested in the small intestine and, therefore, arrive to the large intestine, where they serve as the substrates for saccharolytic bacteria [ 73 ]. Koo et al [ 74 ] found that the supplementation of Thr 15% higher than the NRC recommendation can interact with feed composition to alter gut microbial fermentation. The data also imply that Thr has beneficial effects on intestinal microbiota which might be related to mucin synthesis and immunoglobulin production as a result of Thr addition [ 72 ].…”
Section: The Roles Of Thr On Intestinal Health and Functionsmentioning
confidence: 99%
“…Dietary Thr supply is critical for gut morphological maintenance and development because Thr plays a key role in mucin synthesis and barrier integrity [ 13 , 15 , 41 ]. Ren et al [ 42 ] and Koo et al [ 43 ] both reported that dietary supplementation of Thr above the NRC [ 23 ] requirement enhanced intestinal morphology as reflected in the improved VH, CD, and VCR in weaned pigs. The density of goblet cells in the jejunal villi and crypts was also increased upon dietary Thr supplementation [ 43 ].…”
Section: Amino Acid Effects On Gut Morphologymentioning
confidence: 99%
“…Ren et al [ 42 ] and Koo et al [ 43 ] both reported that dietary supplementation of Thr above the NRC [ 23 ] requirement enhanced intestinal morphology as reflected in the improved VH, CD, and VCR in weaned pigs. The density of goblet cells in the jejunal villi and crypts was also increased upon dietary Thr supplementation [ 43 ]. Either deficiency or excess of dietary Thr has adverse effects on the synthesis of intestinal mucosal proteins such as mucins in young pigs [ 44 ].…”
Section: Amino Acid Effects On Gut Morphologymentioning
confidence: 99%
See 2 more Smart Citations